(untitled) (Itinera, 2024)
In the 21st century, where digital advancements change how we perceive art and aesthetics, there is a need to examine how empirical sciences and the humanities can collaboratively explore these complexities. This paper highlights the reciprocal relationship between these fields, arguing that a fusion of empirical methods and philosophical inquiry can lead to a more comprehensive understanding of aesthetics in the digital age. Empirical sciences bring robust tools for quantifying human experiences, yet they often reduce complex phenomena to measurable parts, potentially missing nuances captured by the humanities. Conversely, the humanities provide deep conceptual insights, but these can benefit from empirical grounding to enhance their applicability and relevance. This interdisciplinary approach is illustrated through the study of digital aesthetics, particularly focusing on the challenges of understanding art and aesthetics across varied human perceptions. Additionally, this paper explores the evolving concept of authorship in the digital age, complicated by AI-generated art and digital mediums. By bridging the strengths of both disciplines, the authors advocate for a more nuanced and evidence-based understanding of these contemporary issues, emphasizing the importance of collaboration in navigating the digital landscape’s complexities.